1998
DOI: 10.1523/jneurosci.18-24-10269.1998
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Opioid Efficacy in Opioid Dependence Is Caused by an Altered Signal Transduction Pathway

Abstract: Chronic morphine administration induces adaptations in neurons resulting in opioid tolerance and dependence. Functional studies have implicated a role for the periaqueductal gray area (PAG) in the expression of many signs of opioid withdrawal, but the cellular mechanisms are not fully understood. This study describes an increased efficacy, rather than tolerance, of opioid agonists at mu-receptors on GABAergic (but not glutamatergic) nerve terminals in PAG after chronic morphine treatment. Opioid withdrawal enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
134
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(144 citation statements)
references
References 39 publications
(68 reference statements)
9
134
1
Order By: Relevance
“…ME-induced GIRK currents are larger and the concentration-response relationship is shifted to the left in rats pretreated with morphine compared to saline. Although supersensitivity of m-opioid receptor coupling to adenylyl cyclase in the PAG has been reported previously (Ingram et al, 1998), it is the first time that supersensitivity has been observed for m-opioid receptor coupling to membrane delimited potassium channels (ie GIRK channels). The increase in GIRK activation is probably evident because morphine is not present.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…ME-induced GIRK currents are larger and the concentration-response relationship is shifted to the left in rats pretreated with morphine compared to saline. Although supersensitivity of m-opioid receptor coupling to adenylyl cyclase in the PAG has been reported previously (Ingram et al, 1998), it is the first time that supersensitivity has been observed for m-opioid receptor coupling to membrane delimited potassium channels (ie GIRK channels). The increase in GIRK activation is probably evident because morphine is not present.…”
Section: Discussionmentioning
confidence: 84%
“…GIRK channels are directly activated by bg subunits (Huang et al, 1995), so an increase in bg release after increased excitatory G as signaling mediated by m-opioid receptors could also increase activation of GIRK channels. Interestingly, m-opioid receptor inhibition of GABA release is potentiated via a G ai -adenylyl cyclase-PKA signaling pathway in rats pretreated with continuous morphine (Ingram et al, 1998) indicating that this m-opioid receptor coupling is not diminished by desensitization. Therefore, it is likely that m-opioid receptors become uncoupled from some effectors (ie membrane delimited potassium channels) more readily than other effectors, (ie adenylyl cyclase) after chronic morphine administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, a cAMP-dependent component of presynaptic inhibition that directly modulates vesicle priming has recently been described (33). Moreover, when cAMP levels increase during withdrawal after chronic exposure to morphine, the p r of GABAergic synapses increases, leading to stronger presynaptic inhibition by morphine (34,35). A similar mechanism appears to operate in ␤-arrestin2 KO mice, which may explain the enhanced efficacy to opioids and its reversal by PKA inhibitors.…”
Section: Pre-and Postsynaptic Inhibition Of Lc Neurons By Morphinementioning
confidence: 95%